Design and evaluation of jamming resilient cyber-physical systems - Tomic,I; Breza,MJ; Jackson,G; Bhatia,L; McCann,JA (IEEE, 2019)
There is a growing movement to retrofit ageing,large scale infrastructures, such as water networks, with wirelesssensors and actuators. Next generation Cyber-Physical Systems(CPSs) are a tight integration of sensing, control, communication,computation and physical processes. The failure of any one ofthese components can cause a failure of the entire CPS. Thisrepresents a system design challenge to address these interde-pendencies. Wireless communication is unreliable and prone tocyber-attacks. An attack upon the wireless communication of CPSwould prevent the communication of up-to-date information fromthe physical process to the controller. A controller without up-to-date information is unable to meet system’s stability and perfor-mance guarantees. We focus on design approach to make CPSssecure and we evaluate their resilience to jamming attacks aimedat disrupting the system’s wireless communication. We considerclassic time-triggered control scheme and various resource-aware event-triggered control schemes. We evaluate these ona water network test-bed against three jamming strategies:constant, random, and protocol aware. Our test-bed results showthat all schemes are very susceptible to constant and randomjamming. We find that time-triggered control schemes are justas susceptible to protocol aware jamming, where some event-triggered control schemes are completely resilient to protocolaware jamming. Finally, we further enhance the resilience ofan event-triggered control scheme through the addition of adynamical estimator that estimates lost or corrupted data.